Quantifying Emergency Department Visits From Sport and Recreation: Focus on the Lower Extremity and Knee, 1997–2009 - Tenan, Matthew S. (Journal of athletic training, 2016)
Few authors have reported nationally representative data on the number of sport and recreation (SR) injuries resulting in emergency department (ED) visitation. The existing studies have only provided 1 or 2 years of data and are not longitudinal in nature.Context: To use a novel algorithmic approach to determine if ED visitation is due to SR, resulting in a substantially larger longitudinal dataset.Objective: Descriptive epidemiology study.Design: Hospital.Setting: The National Hospital Ambulatory Medical Care Survey, a stratified random-sample survey of US hospital EDs was combined for years 1997–2009. There were 15 699 unweighted patient visits determined to be from SR.Patients or Other Participants: A custom algorithm classified SR visits based on the International Classification of Diseases, Ninth Revision, Clinical Modification E-code and pattern recognition of narrative text. Sport and recreation visits were assessed by age and categorized according to broad injury classifications. Additional quantification was performed on SR visits for lower extremity and knee-specific injuries. Sample weights were applied to provide national annual estimates.Main Outcome Measure(s): Annually, 4 243 000 ED visits resulted from SR. The largest classification of injury from SR was sprains and strains (896 000/y). Males had substantially more SR-related ED visits than females (2 929 000/y versus 1 314 000/y). For patients 10–49 years old, 1 093 000 lower extremity and 169 000 knee-specific injury visits annually were from SR. For both injury types, males had a higher rate of ED visitation; however, females had 25% and 39% greater odds of visitation for lower extremity and knee-specific injury, respectively.Results: The burden on the health system of ED visits from SR was substantial. Males presented in the ED at a higher rate for SR injury, though females had a higher proportion of lower extremity and knee-specific injury ED visitations from SR. This longitudinal analysis of population-level data provides the information to target research on specific subpopulations to mitigate SR injury.Conclusions: